Clinical Profile and Treatment Outcomes in Patients Treated with Intensity-Modulated Radiotherapy (IMRT) for Carcinoma Nasopharynx: A Retrospective Analysis. (6th September 2021) - Nazeer, Farida; Rejnish Kumar, R.; Rafi, Malu; Bhattacharya, Tapesh; Mullangath Prakasan, Aparna; Naveen, Kumar P.; George, Preethi; Kunnambath, Ramadas; Thommachan, Kainickal Cessal
Abstract : Objective . To retrospectively evaluate the clinical outcome of carcinoma nasopharynx patients treated with the IMRT technique. Methods . Eighty-one nasopharyngeal carcinoma patients who were treated with IMRT with or without chemotherapy between the period January 2011 and December 2014 at a comprehensive tertiary cancer center, Kerala, India, were included in the study. The mean age was 43 years (range 13–77 years), and majority of the patients were males (67.9%). The stagewise distribution of disease at presentation was 2 (2.5%) in stage I, 19 in stage II (23.5%), 31 (38.3%) in stage III, and 29 (35.8%) in stage IV. All patients were treated using simultaneous integrated boost (SIB) schedule using IMRT with 6 MV photon to a dose of 66 Gy in 30 fractions, 2.2 Gy per fraction prescribed to high-risk PTV; 60 Gy in 30 fractions, 2 Gy per fraction to intermediate risk PTV; and 54 Gy in 30 fractions, 1.8 Gy per fraction to low-risk PTV. Concurrent chemotherapy with cisplatin was offered to patients with stage II and above disease. Neoadjuvant chemotherapy with cisplatin and 5FU was given to patients with initially advanced disease (T3, T4, N2, and N3). Survival estimates were generated using the Kaplan–Meier method. The univariate analysis was performed using log-rank tests. Results . The 5-year locoregional control (LRC), distant metastasis-free survival (DMFS), disease-free survival (DFS), and overall survival (OS) rates were 87.5%, 87%, 61.6%, and 62.5%, respectively. The 5-year OS was 100% for stage I ( n  = 2), 67% for stage II ( n  = 19), 70.4% for stage III ( n  = 31), and 68.1% for stage IV ( n  = 29). The DFS at 5 years was 100% for stage I, 61.1% for stage II, 56.2% for stage III, and 84.8% for stage IV disease. The univariate analysis showed that age, nodal stage, and use of induction chemotherapy showed an improved trend towards OS, though the results were not statistically significant. The predominant pattern of failure in the present study was distant metastasis. Most patients who developed distant metastasis in our study had either an advanced T stage or N3 disease at presentation. Conclusion . The present study shows our initial experience with IMRT for nasopharyngeal carcinoma. The compliance to RT was good in this study. The 5-year LRC and OS rate of nasopharyngeal carcinoma patients treated with IMRT were 87.5% and 62.5%. Distant metastasis was the main pattern of failure.